Hypomethylation within gene promoter regions and type 1 diabetes in discordant monozygotic twins. (April 2016) - Elboudwarej, Emon; Cole, Michael; Briggs, Farren B.S.; Fouts, Alexandra; Fain, Pamela R.; Quach, Hong; Quach, Diana; Sinclair, Elizabeth; Criswell, Lindsey A.; Lane, Julie A.; Steck, Andrea K.; Barcellos, Lisa F.; et al.
Abstract: Genetic susceptibility to type 1 diabetes (T1D) is well supported by epidemiologic evidence; however, disease risk cannot be entirely explained by established genetic variants identified so far. This study addresses the question of whether epigenetic modification of the inherited DNA sequence may contribute to T1D susceptibility. Using the Infinium HumanMethylation450 BeadChip array (450k), a total of seven long-term disease-discordant monozygotic (MZ) twin pairs and five pairs of HLA-identical, disease-discordant non-twin siblings (NTS) were examined for associations between DNA methylation (DNAm) and T1D. Strong evidence for global hypomethylation of CpG sites within promoter regions in MZ twins with TID compared to twins without T1D was observed. DNA methylation data were then grouped into three categories of CpG sites for further analysis, including those within: 1) the major histocompatibility complex (MHC) region, 2) non-MHC genes with reported T1D association through genome wide association studies (GWAS), and 3) the epigenome, or remainder of sites that did not include MHC and T1D associated genes. Initial results showed modest methylation differences between discordant MZ twins for the MHC region and T1D-associated CpG sites, BACH2, INS-IGF2, and CLEC16A (DNAm difference range: 2.2%–5.0%). In the epigenome CpG set, the greatest methylation differences were observed in MAGI2, FANCC, and PCDHB16, (DNAm difference range: 6.9%–16.1%). These findings were not observed in the HLA-identical NTS pairs. Targeted pyrosequencing of five candidate CpG loci identified using the 450k array in the original discordant MZ twins produced similar results using control DNA samples, indicating strong agreement between the two DNA methylation profiling platforms. However, findings for the top five candidate CpG loci were not replicated in six additional T1D-discordant MZ twin pairs. Our results indicate global DNA hypo methylation within gene promoter regions may contribute to T1D; however, findings do not support the involvement of large DNAm differences at single CpG sites alone in T1D. Highlights: T1D discordant MZ twins differentially methylated within/near established T1D genes. Evidence for global hypomethylation of gene promoter CpGs in cases versus controls. T1D discordant HLA-identical sibs show different methylation patterns than MZ twins. Illumina's 450k array results validated by pyrosequencing of control DNA samples. Replication dataset suggests single CpG methylation differences not related to T1D.